2007
DOI: 10.1212/01.wnl.0000265591.10200.d7
|View full text |Cite
|
Sign up to set email alerts
|

Post-transplant acute limbic encephalitis

Abstract: Patients undergoing allogeneic hematopoietic stem cell transplantation are at risk for post-transplant acute limbic encephalitis (PALE), a distinct neurologic syndrome. Treatment considerations should include aggressive seizure control and, possibly, antiviral therapy. PALE can be associated with the CSF presence of human herpesvirus-6, but the pathogenic role of the virus requires further exploration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
208
2
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 260 publications
(220 citation statements)
references
References 38 publications
9
208
2
1
Order By: Relevance
“…3,36,37 Overt seizures, including generalized seizures and partial seizures, develop in 40-70% of patients. [36][37][38] HHV-6 encephalitis may accompany syndrome of inappropriate antidiuretic hormone. [38][39][40] HHV-6 encephalitis typically shows an MRI signature of hyperintense lesions on T2-weighted, fluid-attenuated inversion recovery imaging and diffusion-weighted imaging of bilateral medial temporal lobes, primarily affecting the hippocampus and amygdala (Figure 1).…”
Section: Disease Associations: We Do Not Know the Precise Disease Assmentioning
confidence: 99%
See 1 more Smart Citation
“…3,36,37 Overt seizures, including generalized seizures and partial seizures, develop in 40-70% of patients. [36][37][38] HHV-6 encephalitis may accompany syndrome of inappropriate antidiuretic hormone. [38][39][40] HHV-6 encephalitis typically shows an MRI signature of hyperintense lesions on T2-weighted, fluid-attenuated inversion recovery imaging and diffusion-weighted imaging of bilateral medial temporal lobes, primarily affecting the hippocampus and amygdala (Figure 1).…”
Section: Disease Associations: We Do Not Know the Precise Disease Assmentioning
confidence: 99%
“…[38][39][40] HHV-6 encephalitis typically shows an MRI signature of hyperintense lesions on T2-weighted, fluid-attenuated inversion recovery imaging and diffusion-weighted imaging of bilateral medial temporal lobes, primarily affecting the hippocampus and amygdala (Figure 1). 3,7,[36][37][38]41,42 Some investigators have termed this finding 'post-transplant acute limbic encephalitis (PALE) 38,40,[42][43][44] and HHV-6 PALE has been diagnosed when the patient has detectable HHV-6 DNA in cerebrospinal fluid in the context of acute-onset altered mental status, amnesia, seizures or other evidence of medial temporal lobe disease involving the limbic system and no other identifiable etiology. 38,42 A recent retrospective study 45 showed, however, not all cases of HHV-6-associated CNS dysfunction meet the criteria for PALE.…”
Section: Disease Associations: We Do Not Know the Precise Disease Assmentioning
confidence: 99%
“…[19][20][21] HHV-6 encephalitis can result in serious neurological sequelae, such as biphasic seizures and other symptoms of post-transplant acute limbic encephalitis. [22][23][24][25] Symptoms often include confusion, seizures, delirium, aphasia, amnesia, emotional outbursts, hypersexuality, hemiparesis, hemiplegia, ataxia, hyperreflexia, syndrome of inappropriate diuretic hormone secretion and electroencephalography abnormalities. 22,23 HHV-6 encephalitis is also associated with a high rate of long-term sequelae and mortality.…”
Section: Introductionmentioning
confidence: 99%
“…[22][23][24][25] Symptoms often include confusion, seizures, delirium, aphasia, amnesia, emotional outbursts, hypersexuality, hemiparesis, hemiplegia, ataxia, hyperreflexia, syndrome of inappropriate diuretic hormone secretion and electroencephalography abnormalities. 22,23 HHV-6 encephalitis is also associated with a high rate of long-term sequelae and mortality. In a review of post-transplant acute limbic encephalitis associated with HHV-6, Seeley et al 23 found that 5 out of 9 (56%) HHV-6 þ post-transplant acute limbic encephalitis patients died, while 3 out of 4 (75%) of the surviving patients maintained persistent cognitive impairment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation